Financial intermediation, infrastructure investment and regional growth. Issue 3 (2nd September 2017) - Clark, Gordon L.
ABSTRACT: Over the past 25 years or so, regional banks and related savings organizations have lost out to new forms of saving and investment. The recent successes and failures of financial intermediation and markets are noted, along with arguments to the effect we are in the midst of a global savings glut. The paper provides a stylized account of how new kinds of financial intermediaries have begun to fill the vacuum left by traditional intermediaries. Implications are drawn for European urban and regional growth in circumstances where financial intermediaries have sought to realize the value embedded in urban infrastructure.